PENGEMBANGAN PEGAWAI DALAM MENINGKATKAN SUMBERDAYA MANUSIA PADA BADAN KEPEGAWAIAN PENDIDIKAN DAN PELATIHAN DAERAH KABUPATEN GORONTALO - Widya Kurniati Mohi (Publik : (Jurnal Ilmu Administrasi), 2015)
The research method used descriptive method, that can be interpreted as a problem solving process were investigated by describing the state of subject and object of research at the present time based on the facts that appear or how (Hadari Nawawi, 1990). The interesting conclusion research, that employee affair Board Education And Training in Bone Bolango regency do the continue development of the employees quality through the education and training, it is done in order to build the capacity of staff based on the demands of the national and global challenges to achieve good governance . On implementation of the development program of the most dominant factor that can determine what or not the development is done comes from the motivation of the participants as well as the development of science and technology. Motivation of participants to determine what or not the current development is done, while the development of technology that encourages each agency or organization to continue to make efforts to develop the quality of its employees. Suggested to the employee affair Board Education and Training in Bone Bolango regency, in determining the development of the participants should have held a more stringent selection, in order to get the participants were really ready to follow in order to improve the development of human resources.